Intercropping cactus and sorghum under agroecological transition and water restriction increases the water productivity of the system regardless of the arrangement of the genotypes - Silva, Thieres George Freire da; Jesus, Eli Lino de; Reis, Marine Cirino Grossi; Klink, Annik Frasso Corrêa; Araújo Júnior, George do Nascimento; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Alves, Cleber Pereira; Morais, José Edson Florentino de; Souza, Carlos André Alves de; Santos, Agda Raiany Mota dos; Silva, Gabriel Ítalo Novaes da; Araújo, Jandis Ferreira Nunes de; et al. (Elsevier, 2024)
The agroecological transition is an important step in changing from a conventional to agroecological production system. The cactus-sorghum intercropping can be recommended for the agroecological transition in a semi-arid environment depending on the cultivation configuration, that is, the type of forage cactus clone and sorghum cultivar. This study aimed to evaluate the effect of intercropping forage cactus clones (Nopaleae spp. and Opuntia spp.) with sorghum cultivars (Sorghum bicolor) on water use efficiency compared with single crops, to recommend the use of intercropping systems in conventional production units under agroecological transition. The study was conducted in the district of Serra Talhada, Pernambuco, Brazil over three crop seasons between 2017 and 2022, using cactus clones and sorghum cultivars in single-crop and intercropping configurations. The forage cactus clones evaluated were: IPA Sertania (IPA, Nopalea cochenillifera), Miuda (MIU, Nopalea cochenillifera), and Orelha de Elefante Mexicana (OEM, Opuntia stricta), while the sorghum cultivars evaluated were IPA 467, IPA SF11 and IPA 2502. The components of the soil water balance and dry matter yield were determined to calculate the following water indices: water use efficiency (WUE), water productivity of the production system (WPcR+ID), crop water productivity (WPCETa), and irrigation water productivity (WPID). Including sorghum and cactus production system under water deficit increased the water productivity of the system due to the increase in dry matter (616 %). Regardless of the cactus clone or sorghum cultivar, there was an increase of 593 % in terms of WPcR+ID, 597 % in terms of WPCETa and 593 % in terms of WPID, with little reduction in WUE (−2 %). The intercropping systems comprising the OEM clone and sorghum 288, OEM clone and sorghum 467, and the IPA clone and sorghum 467 showed a high level of crop water productivity due to the reduction in actual evapotranspiration. It can therefore be said that optimising the use of water in cactus systems under agroecological transition and water restriction depends on the type of cactus clone and sorghum cultivar.
Keywords: Drought; Forage cactus; Sorghum; Water productivity; Water use efficiency